Relationship between work context and sleep problems of high school teachers (Research, Society and Development, 2021)
Objective: The teaching function is related to work overload and health problems, including sleep problems. However, is there a relationship between sleep problems and aspects of work? In view of this, this study aimed to assess the relationship between the work context, the quality of sleep and the daytime sleepiness of teachers from public schools in Rio Grande do Norte (RN). Methodology: This study was conducted in 9 schools with 61 teachers of both genders who filled the work context assessment scale, the Pittsburgh Sleep Quality Index and the Epworth Sleepiness Scale. Results and Discussion: The majority evaluated Working Conditions and Work Organization as critical/severe, and half of them considered Socio-Professional Relations as critical/severe. Poor sleep quality was observed in 69% of teachers, regardless of gender and excessive daytime sleepiness was observed in 49% of teachers, most often in women (55%) compared to men. Nevertheless, there was no significant relationship between work context and sleep problems. In relation to sleep schedule, it was observed that teachers present late sleep time (23: 26 ± 1: 25h) and early wake up time (6: 06 ± 1: 16h) which may have resulted in short sleep duration (6: 10 ± 1: 07h). Conclusion: These results demonstrate that, in general, public school teachers in RN present complaints related to the work context and sleep problems. However, studies with a more representative sample are needed to assess as the factors related to the work context may be contributing to sleep problems. Furthermore, there is a need to create spaces for discussion with teachers in order to improve the work context and public policies aimed at education.